Surface-enhanced Raman-based quick detection method for flavin protein progeny - TIAN YAPING; TIAN KANGZHEN; NIE XINMING (2020)
The invention discloses a surface enhanced Raman spectroscopy (SERS)-based method for quickly detecting a flavin protein prothetic group. The method comprises the following steps: directly collectingan SERS signal of a flavin protein auxiliary group; the method provided by the invention is simple to operate and label-free, and the detection capability on the flavin protein progeny can reach 0.1 mg/L, so that the detection sensitivity is higher and more stable, the influence of external temperature and a sample on qualitative detection is greatly reduced, the detection is more convenient, andthe operation process is simple. And a new method can be provided for real-time monitoring of biological medicine and food production. 本发明公开了一种基于表面增强拉曼光谱（SERS）的黄素蛋白辅基的快速检测的方法，该方法是直接采集黄素蛋白辅基的SERS信号,发明操作简单并且免标记，对黄素蛋白辅基的检测能力可以达到0.1mg/L，可以使检测的灵敏度更高、更稳定，大大减少了外界温度、样品本身对检测定性的影响，使检测更便捷，操作过程简单。可以为生物医药和食品生产的实时监测提供一种新的方法。